Efforts To Return The Charm Of Kamasan Klungkung Art Village - Latif, B Syarifuddin; Demolingo, Ramang H; Christiani, Meiliana (CV ODIS, 2024)
The research that will be carried out in Klungkung Regency aims to learn more about the Balinese Gandrung dance which is starting to fade. Many people know the Gandrung dance, not from Bali but from East Java Province. This is the stimulus this research is based on. Namely to introduce the Gandrung dance belonging to Bali Province, so that later this research will be able to revive Klungkung Regency Tourism through the charm of Dance, especially the Gandrung dance. This research also aims to explore aspects of Gandrung Dance as a learning resource for the History of Balinese Dance Culture. This research uses a social approach, namely by looking for sources of informants, either through community figures or art masters in Bali, then data collection techniques using observation, interviews, document study, and analyzing data. The method that will be used is a qualitative method which will focus on observations that will be carried out in Klungkung Bali. In this research, the expected target is that the Kamasan Arts Village in Klungkung Regency can return to life by empowering the charm of dance performing arts. The objectives of this research are: 1) To introduce the wider audience to the Gandrung dance from Bali. 2) Become a learning medium to preserve Gandrung dance and knowledge about the history of dance in Bali. 3) Showing the wealth of intangible heritage belonging to Indonesia, especially Bali. 4) Become a new show attraction for Bali tourism.